Frontal Underactivation During Working Memory Processing in Adults With Acute Partial Sleep Deprivation: A Near-Infrared Spectroscopy Study - Yeung, Michael K.; Lee, Tsz L.; Cheung, Winnie K.; Chan, Agnes S. (Frontiers in Psychology, 2018)
Individuals with partial sleep deprivation may have working memory (WM) impairment, but the underlying neural mechanism of this phenomenon is relatively unknown. The present study examined neural processing during WM performance in individuals with and without partial sleep deprivation using near-infrared spectroscopy (NIRS). Forty college students (10 males) were equally split into Sufficient Sleep (SS) and Insufficient Sleep (IS) groups based on self-reports of previous night’s sleep duration. Participants in the SS group obtained the recommended amounts of sleep according to various sleep organizations (i.e., > 7.0 hr), whereas those in the IS group obtained amounts of sleep no greater than the lower limit of the recommendation (i.e., ≤ 7.0 hr). All participants underwent an n-back paradigm with a WM load (i.e., 3-back) and a control condition (i.e., 0-back) while their prefrontal hemodynamics were recorded by NIRS. The IS and SS groups performed the tasks comparably well. However, unlike the SS group, which exhibited bilateral frontal activation indicated by increased oxyhemoglobin concentration and decreased deoxyhemoglobin concentration during WM processing (i.e., 3-back > 0-back), the IS group did not exhibit such activation. In addition, levels of WM-related frontal activation, especially those on the left side, correlated with sleep duration the night before, even when habitual sleep duration was controlled for. The findings suggest the presence of frontal lobe dysfunction in the absence of evident WM difficulties in individuals with acute partial sleep deprivation. They also highlight the importance of a good night’s sleep to brain health.